Representation of women in authoritarian Chile. An approach from advertising - Vergara Leyton, Enrique; De Simone, Liliana; Gómez-Lorenzini, Paulina; Labarca, Claudia; Guevara-Iturbe, Antonia (Historia y Comunicación Social, 2024)
The objective of this article is to analyze advertising directed at women in the context of the dictatorship in Chile (1973-1990). In retrospect, advertising constitutes a valuable testimonial resource and is an eloquent expression of the transformations that Chile underwent during the authoritarian regime before neoliberalism expanded to other regions. Using a mixed methodology that combined content analysis and semiotics, the results reveal a modernizing emphasis within the female consumer imaginary, associated with the values of the imposed neoliberal order that positioned consumption as one of the main drivers of social relations. However, this proposal did not significantly alter the roles that advertising has traditionally assigned to women. The conclusion drawn is that advertising reflects both the modernizing dynamics of the time as well as the contradictions and conflicts inherent in the stereotypical representation of women in the media.